1997
DOI: 10.17660/actahortic.1997.448.24
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rootstock on the Mineral Concentrations of Flowers and Leaves From Sweet Cherry

Abstract: The influence of rootstock on the mineral composition of scion leaves of fruit trees is generally accepted. The present work was carried out to corroborate if this influence is also evident for the mineral nutrient concentrations in flowers. The study was made in an experimental orchard of sweet cherry (Prunus avium, L. cv. 'Van') grafted on three rootstocks: Adara, SL 64 and Cok. Flowers and leaves were sampled at full bloom and 60 days after fuil bloom (DAFB) respectively. They were analyzed for nitrogen (N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Micronutrient concentration was significantly influenced by rootstock. As previously reported (15), the Fe concentration in flowers was greater on SL 64, probably due to the better adaptation of P. mahaleb species in calcareous soils. Flower Mn concentration was highest on P. cerasus rootstocks (CAB 6P, CAB 11E and MM 9), especially when compared with MaxMa 97, MaxMa 14 and SL 64.…”
Section: Floral Mineral Nutrientssupporting
confidence: 84%
“…Micronutrient concentration was significantly influenced by rootstock. As previously reported (15), the Fe concentration in flowers was greater on SL 64, probably due to the better adaptation of P. mahaleb species in calcareous soils. Flower Mn concentration was highest on P. cerasus rootstocks (CAB 6P, CAB 11E and MM 9), especially when compared with MaxMa 97, MaxMa 14 and SL 64.…”
Section: Floral Mineral Nutrientssupporting
confidence: 84%
“…In addition, Zarrouk et al (2005) indicated that only flower Zn concentration in peach was significantly correlated with Zn in leaves, as opposed to the other nonsignificant correlations. Similar data were reported by Sanz and Montañés (1995) for peach and Betrán et al (1997) and Jiménez et al (2004) for cherry. A PCA, one of the multivariate statistical procedures, was used to establish relationships among shoots, flower buds and flowers and to study correlations regarding Na content within sets of rootstock/cultivar combination.…”
Section: Evaluation Of Correlations Among Variables and Principal Comsupporting
confidence: 86%
“…There were statistically significant differences (P ≤ 0.05) in the present study among rootstock/cultivar combinations in Na content of (Figure 4). Betrán et al (1997) reported that the range of variation of Na ion in flowers, among rootstocks, was higher than leaves and other organs. Additionally, apart from rootstock, species and/ or genotypes play a key role in determining the Na content in the flowers of fruit crops, which is in agreement with previous work in flower (ZARROUK et al, 2005).…”
Section: Content Of Sodium (% Of Dry Weight)mentioning
confidence: 99%
“…Interestingly, Moreno et al (1996Moreno et al ( , 2001 reported that sweet cherries on Colt grown on heavy and calcareous soil showed deficiency or close to deficiency values for N and K, and values higher than normal for Ca and Mg at 60 DAFB. On this line, Betrán et al (1997) (Tisdale, Nelson 1966). Al- (Leece 1975); (-) lower content than optimum; (+) higher content than optimum; the different letters in last column indicate significant differences among ΣDOP indexes within each cultivar at P ≤ 0.05 by the LSD test; DAFB -days after full bloom; DOP -deviation from optimum percentage though overall Fe levels were very deficient, the Fe present may have been quite active physiologically (Leece 1975).…”
Section: Dop and σDop Indexesmentioning
confidence: 99%
“…According to Betrán et al (1997), the standard sampling time for cherry foliar diagnosis is usually assessed at mid-summer, i.e. approximately at 120 days after full bloom (DAFB).…”
Section: Leaf Nutrient Composition At 60 Dafbmentioning
confidence: 99%